EXPLORING THE ROLE OF DRUGBANK IN INVESTIGATING PHARMACOGENOMIC-DRIVEN NOVEL DRUG - Santoso, Setiyo Budi; Pribadi, Prasojo; Hapsari, Widarika Santi; Abiyana, Setya Rini (Jurnal Farmasi Sains dan Praktis, 2025)
Bioinformatics plays a vital role in drug discovery and repurposing, yet challenges persist in data availability, biological complexity, and method standardization. The continued exploration and utilization of resources such as DrugBank will play a crucial role in advancing drug development and uncovering novel therapeutic opportunities. Our study presents a comprehensive analysis of the methodology utilized by bioinformaticians to integrate DrugBank with multiple databases, with the aim of facilitating the discovery of novel drugs. A literature review was conducted using Scopus and PubMed, focusing on articles from the last 10 years. Relevant articles meeting the inclusion criteria were collected between October and November 2022. The review identified 35 unique papers after removing duplicates. Screening led to 9 papers meeting inclusion criteria. The study reveals that DrugBank is an indispensable resource, aiding drug-gene interaction analysis and connecting gene data sources with potential drug candidates. It streamlines the multinetworking process and enables the identification and validation of new medications through clinical tools. These findings shed light on drug-gene interactions and drug repurposing, emphasizing the significance of leveraging multiple databases and network data. DrugBank's pivotal role in advancing drug discovery and personalized medicine underscores its importance in bioinformatics research.